Use of foreign experience in the hospitality and tourism industry in the Republic of Kazakhstan - Alekseenko, T.N.; Jazykbayeva, B.K.; Huszti, Z. (BUKETOV BUSINESS REVIEW, 2019)
The article is aimed at identifying foreign experience in the development of the hospitality and tourism industry and the possibilities of its use in Kazakhstan. It is noted that the concepts of hospitality and tourism are two interrelated terms. Tourists are potential consumers who have a variety of desires and needs, depending on the purpose of their travel. Hospitality and tourism industry is generally regarded as one of the key driving forces of national and regional economic development. The key actors in hospitality and tourism development are the state, market, tourists and local people. The interactions among these actors create both public and social institutions together with market mechanisms. Success in the tourism and hospitality sector also depends on nurturing a quality workforce that is capable of delivering excellent customer service. In conclusion of this part, it is clearly seen, that the governments play the most important role in hospitality and tourism industry development. The government has to control development of the industry. On the Kazakhstani market of educational services the activity on preparation of specialists for tourism — a relatively new phenomenon. The analysis of activity of the Kazakhstani tourist firms, hotels and restaurants shows that the level of personnel training and quality of services lag behind generally accepted international standards in the West. Educational standards for the training of personnel for tourism industry are also varied considerably with educational standards of Europe. Taking into account the world experience of personnel training in the field of tourism industry and in accordance with generally accepted international standards, possibly to consider the introduction in Kazakhstan of such directions of training of competent professionals at the level of postgraduate education as «Management of hospitality». It is revealed that the study of world experience and its application in Kazakhstan is important for the successful development of the domestic hospitality and tourism industry.